Digitalization Of Mother And Child Health Book (KIA) at Posyandu Anggrek IV Kalisari - Divia Sekar Tanjung; Desi Novianti; Dyah Rhetno Wardhani; Adhityo Kuncoro (Journal of Information System, Informatics and Computing, 2022)
Posyandu is a collection of people who get together to assist the community, and posyandu is a space or container where health services are improved and distributed. Almost all activities have been digitized in the contemporary industrial era 4.0, and posyandu should have begun to be digitized as well. Patients frequently do not carry a Maternal and Child Health (MCH) book, and the data gathering mechanism at the Kalisari Orchid IV Posyandu is still manual. This research intends to improve the efficiency of posyandu cadres so that they don't waste time and energy. Also, make it easier for the public so that they don't have to carry the MCH book and may read the examination results without having to open the MCH book. The author employed observation, interviews, and a literature review to obtain data for this study. With Java as the programming language, Netbeans IDE 8.0.2 as the editor, and MySQL as the database As a result of this study, the data collection procedure becomes more efficient and organized. The reporting process can then become faster and more organized. Patients benefit as well because they can track their progress even if they don't have or have an MCH handbook.